Some Uncomfortable Arithmetic Regarding Europe's Public Finances - Velculescu, Delia (IMF Working Papers; Working Paper ;, 2010)
Traditional fiscal indicators focused on measures of current deficits and debt miss the potentially important implications of current policies for future public finances. This could be problematic, including in the case of Europe, where population aging is expected to pose additional fiscal costs not captured by such indicators. To better gauge the state of public finances in the EU27 countries, this paper derives forward-looking fiscal measures of intertemporal net worth both directly from the European Commission's Aging Working Group's long-run indicators and using a comprehensive public-sector balance sheet approach. These measures could be used as an "early warning" mechanism and also as a communication device with the public. Current estimates indicate that, on existing policies, the intertemporal net worth of the EU27 is deeply negative, even in excess of its GDP level, and is projected to worsen further over time. This suggests that Europe's current policies need to be significantly strengthened to bring future liabilities in line with the EU governments' capacity to generate assets.